UNDERSTANDING THE COMPLEXITY OF CHILD SOLDIER RECRUITMENT PROBLEMS IN SUDAN - Riyadi, Maskur (Journal of Terrorism Studies, 2025)
This study examines human rights violations in the recruitment of child soldiers in Darfur, Sudan, where more than 300,000 boys and girls under the age of eighteen were recruited by government armed forces, militias, or non-state armed groups. Using a qualitative literature study, this study aims to examine the factors behind the recruitment of child soldiers and examine the phenomenon using international humanitarian law. This study concludes that the recruitment of child soldiers is caused by competition for limited natural resources, easy access to weapons, and unequal levels of education and economy. The violations found based on humanitarian law are; 1) violating the minimum limit for child soldier recruitment by the state, which is 18 years (Article 2 of the Optional Protocol); 2) violating the minimum limit for child recruitment by non-government armed groups, namely 18 years (Article 4 of the Optional Protocol), 3) violating the conditions for voluntary recruitment of child soldiers (Article 3 paragraph (3) of the Optional Protocol).